Knowledge Regarding Reproductive Health among Adolescent - Kili Astarani; Selvia David Richard; Dian Taviyanda; Sharon Rose; Michelle Paulina Amallo (Genius Journal, 2023)
Introduction: Reproductive health is a very important aspect for all men and women, including teenagers, to know. The phenomenon shows that some teenagers do not know and understand reproductive health, for example, menstruation and pregnancy Objective: This research aims to determine adolescent knowledge about reproductive health and then their knowledge and attitudes toward reproductive health problems. Methods: This research is a descriptive study with the variable knowledge of adolescent reproductive health. The population of this study was young men and women aged 10 to 19 years, totaling 39 people. The sampling technique is total sampling. The instrument used for data collection is a questionnaire, which consists of general data and specific data. General data includes biodata, general information about adolescent reproductive health, and information sources used by adolescents to obtain information about adolescent reproductive health. Data analysis was carried out quantitatively and adjusted to the objectives to be achieved in the research. Results: knowledge about adolescent reproductive health at the Kasih Allah Tulungagung Orphanage was in the sufficient category of 11 respondents (28.21%) and the insufficient category was 28 respondents (71.79%). Conclusion: Knowledge about adolescent reproductive health at the Kasih Allah Tulungagung Orphanage is in the poor category. Knowledge of adolescent reproductive health is very important so that adolescents have responsible behavior